Efficacy of cold atmospheric pressure plasma jet against Enterococcus faecalis in apical canal of human single-rooted teeth: A preliminary study - K. Saleewong (2020)
© Published under licence by IOP Publishing Ltd. Many factors that may affect the success of root canal treatment are complexity of root canal system, especially in the apical part, and the virulence of bacteria such as biofilm formation. A cold atmospheric pressure plasma jet is a novel method for sterilization and applied for root canal disinfection. The purpose of this study was to investigate the effect of the cold atmospheric pressure plasma jet on Enterococcus faecalis (E. faecalis) biofilms infected in the apical root canals. Methods: Fifty-four single rooted-teeth were infected with E. faecalis for seven days and allocated into five groups. Group I performed as positive control. Group II-V were served as experimental groups: NaOCl, plasma, NaOCl + plasma and gas only, respectively. The disinfection was evaluated by colony count (per milligram) at the depths of 0.05 and 0.10 mm of root dentin. The remaining bacteria was also counted from the grounded root dentin. Data was analysed by one-way ANOVA and post hoc test, with a level of significance set at P<.05. Results: The NaOCl, plasma and NaOCl + plasma groups significantly reduced the E. faecalis, but no significant difference was found among these groups (P>0.5). The NaOCl + plasma group significantly reduced E. faecalis in the deeper dentin level compared to the other groups. Conclusion: The cold atmospheric pressure plasma jet had antimicrobial activity against E. faecalis biofilm as well as the use of NaOCl. The combined treatment yielded the most promising result and may be beneficial in root canal disinfection.